2017
DOI: 10.1063/1.4974096
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of local symmetry correlators for interacting many-particle systems

Abstract: Recently (PRL 113, 050403 (2014)) the concept of local symmetries in one-dimensional stationary wave propagation has been shown to lead to a class of invariant two-point currents that allow to generalize the parity and Bloch theorem. In the present work we establish the theoretical framework of local symmetries for higher-dimensional interacting many-body systems. Based on the Bogoliubov-Born-Green-KirkwoodYvon (BBGKY) hierarchy we derive the equations of motion of local symmetry correlators which are offdiago… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…We also think that our results further underline the important role played by symmetries in molecular theories of the one-body reduced density matrix 64,[75][76][77] . All our findings can be rewritten in linear response theory, such that the computational burden can be further relieved.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We also think that our results further underline the important role played by symmetries in molecular theories of the one-body reduced density matrix 64,[75][76][77] . All our findings can be rewritten in linear response theory, such that the computational burden can be further relieved.…”
Section: Discussionsupporting
confidence: 67%
“…The missed diagonal terms ϕ k |φ k can be removed as convenient phase factors 64 (see below). The equations of motion of ξ and f can be derived from the stationary condition of the time-dependent quantum mechanical action…”
Section: A Formula For the Time Evolution Of The Fermionic Occupmentioning
confidence: 99%
“…Furthermore, recently it has been shown that these currents are obtained, as a special case, from a more general continuity equation involv-ing currents constructed from wave fields satisfying two different wave equations [10]. Even more, as shown in [10][11][12] such currents can be defined for arbitrary spatial dimensions d and number of degrees of freedom N . The only significant change for d > 1 is that these generalized currents are not spatially constant any more but they possess a vanishing divergence.…”
Section: Introductionmentioning
confidence: 99%
“…on the invariance of a subset of matrix elements under a site permutation. In general, local symmetries of the underlying Hamiltonian are indirectly encoded into its eigenstates, as has been demonstrated recently in various contexts [30][31][32][33][34][35][36][37][38]. However, not every locally symmetric system features CLSs, and a systematic framework linking a theory of local symmetries to the formation and control of both CLSs and the resulting flat bands is still missing.…”
Section: Introductionmentioning
confidence: 99%